KESETARAAN PERAN ANTARA LAKI LAKI DAN PEREMPUAN DALAM IKLAN TELEVISI - Qoute Nuraini (Media Bahasa, Sastra, dan Budaya Wahana, 2021)
AbstractThis research is about the equality of roles between women and men in television advertisements in Indonesia. The research method uses descriptive content analysis. In this study used thematic recording units and context. The thematic recording unit in the form of equality of roles between women and men in television commercials. Recording units are formulated with operational access, participation, control, and benefits. As well as verbal and non verbal messages in the advertisementsThe population in this study is television advertisements during period December 2020 - January 2021 which amounted 102 advertisements. The sample units in this study obtained 3 advertisements that have the value of equality of roles between women and men. Sampling techniques using purposive sampling techniques The validity used in this study is the the face validity that checks and ensures that the size used matches what you want to measure. Researchers checked e-books Gender Equality parameters in the formation of legislation issued by the Ministry of Women Empowerment and Child Protection of the Republic of Indonesia, the Ministry of Home Affairs of the Republic of Indonesia and the Ministry of Law and Human Rights of the Republic of Indonesia. The reliability used in this study is its reproductionability. Reliability findings as much as 0.94%, this result is said reliable.The results found that in the verbal and non verbal advertising messages the three advertisement  could be found the value of equality of women's and men's roles. The element of access is the most found in verbal and nonverbal messages that is as much as 31%, the element of participation is found as much as 25% (in verbal and nonverbal messages), the control element as much as 21.5% in verbal messages and non verbal advertising, the last element is the benefit as much as 21% (verbal and non verbal messages).Keywords: Equality of women and men's roles, verbal and non verbal messages, advertising